Water Tourism Potential Science E-Book As A Development Product For Elementary School Learning - Oktaviasari, Ikke; Sofiyana, Marinda Sari; Rosyida, Desy Anindia (Universitas Islam Balitar, 2024)
The ICT development today is spurring elementary school students' learning in classroom, so they have analytical skills, critical thinking, and superior competence. Good learning must be carried out with the learning objectives. Researchers carried out preliminary observations for obtaining the needs of teachers and students in learning science in elementary schools in Blitar. Observation findings state that teachers tend to use conventional teaching materials and students tend to get bored in visualization-based learning, like water cycle material in sciences. Researchers propose research and development for products in form of Science E-Books about the potential for water tourism to spur student achievement in water cycle material. Researchers carry out 7 out of 10 stages of research only because of limited time, manpower, and funds. Design production is validated by material, media, and language experts with respective average scores of 86%, 84%, and 91%, all of which are classified as valid. Then researcher also carried out product readability test on teachers and students with an average score of 96% and 87%, all of which were also valid. Thus, the development of the Science E-Book can be used by teachers to spur student achievement in science learning on the water cycle material.